'Mali Matters': reflections on a leadership and quality improvement project to improve blood transfusion safety at Maluti Adventist Hospital, Mapoteng, Lesotho. Issue 2 (22nd October 2021) - Snead, Charlotte M; Upton, Rebecca J; Ranaivoarijaona, Gilbert S V N; Luthango, Ellen
Abstract : Introduction: This report outlines a quality improvement (QI) project aiming to improve blood transfusion safety at Maluti Adventist Hospital (MAH), Lesotho, from August 2019 to January 2020. The project team comprised nine local staff members and two UK doctors working through the NHS 'Improving Global Health through Leadership Development' (IGH) programme. Methods: Baseline data was gathered and a 'process mapping' meeting held to understand existing processes and identify methods for improvement. Improvements were implemented using Plan-Do-Study-Act (PDSA) methodology. The NHS Healthcare Leadership Model was used as a framework for leadership development and team members reflected on their personal learning. Results: Varied interventions included introduction of a pre-transfusion bedside safety checklist and staff training. Documentation of critical patient identifiers for transfusion improved. Completion of the bedside safety checklist was 65.5% by 3 months. Knowledge scores improved post-transfusion training. 77% of staff strongly agreed and 21% agreed that the training was useful. Challenges and further work were reflected on. Discussion: This collaborative system-strengthening project provided varied, reciprocal learning experiences including skills in leadership, teamwork, teaching, QI methodology, communication and IT. Our experiences will help to inform ongoing work at MAH and may be helpful to others conducting similar work in related settings.